O papel do empreendedor no desempenho internacional de uma empresa de base tecnológica - Nogueira, Guilherme Mazzaro (2023)
The present dissertation proposed to analyze the role of the entrepreneur in the international performance of the technology-based company. For this, a single case study was carried out with a startup in the e-commerce sector that is internationalizing its operations through the StartOut Brasil program, focusing on the United States of America market. The analysis of the collected data was done through content analysis, using Microsoft Excel software. With regard to the specific objectives of the study: Present the company studied according to the profile and process of internationalization; Identify the dimensions present in the company's internationalization process; Identify the international performance of the studied company; Check whether there is an association between the role of the entrepreneur and the international performance of the technology-based company. Throughout the analysis, all objectives were answered and the propositions made were confirmed, resulting in the following responses: The startup has notoriety in the national panorama with recognition by awards and top investors. With the mastery of its technology on behalf of entrepreneurs, it is seeking opportunities in the foreign market. Aiming to keep costs and risks under control, the company participates in government programs to accelerate internationalization to gain knowledge and success in its endeavor. Among the main contributions to the field of International Entrepreneurship, this dissertation seeks to contribute to the understanding of what the internationalization process of a technology-based company is, contributing to the development of knowledge on the subject. Also under the managerial panorama, it can serve as a source of consultation for managers who seek to internationalize their business under conditions similar to those described in the case study. As limitations to the study, it can be highlighted the fact that it is a study that seeks depth in the richness of details of a phenomenon, which in turn makes it difficult to extrapolate the results to other scenarios. As a suggestion for future research, we highlight the study with multiple cases or with two companies from different countries in order to carry out a comparative study.